2013
DOI: 10.1053/j.ajkd.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Associations of Urine Protein-Creatinine Ratio Versus Albumin-Creatinine Ratio With Complications of CKD: A Cross-sectional Analysis

Abstract: Background Urine albumin-creatinine ratio (ACR) and protein-creatinine ratio (PCR) are important markers of kidney damage and are utilized for prognosis in persons with chronic kidney disease (CKD). Despite how commonly these measurements are done in clinical practice, relatively few studies have directly compared the performance of these two measures with regard to associations with clinical outcomes, which may inform clinicians about which measure of urinary protein excretion is best. We studied the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Some other reports suggested that protein-to-creatinine ratio was comparable with ACR (17,25). Regarding proteinuria measurement, recommendations from different guidelines are also different.…”
Section: Discussionmentioning
confidence: 95%
“…Some other reports suggested that protein-to-creatinine ratio was comparable with ACR (17,25). Regarding proteinuria measurement, recommendations from different guidelines are also different.…”
Section: Discussionmentioning
confidence: 95%
“…study, medication and protein intake data were not available . Furthermore, neither considered the relationship between serum bicarbonate and albuminuria, which seems to be higher in those with low bicarbonate and could influence the associations described . While the study by Moranne et al .…”
mentioning
confidence: 97%
“…Our group previously reported that the PCR is highly correlated with the ACR and that an ACR of 30 mg/g creatinine is equivalent to a PCR of approximately 0.08-0.09 g/g creatinine, based on the analyzed datasets (Yamamoto et al 2011(Yamamoto et al , 2014. Fisher et al (2013) reported that the ACR and PCR are relatively similar and that an ACR of 30 mg/g creatinine is equivalent to a PCR of approximately 0.08-0.11 g/g creatinine based on regression and Lowess smooth analyses in a recent large CKD cohort study. These results imply that the PCR cut-off is not precisely equal to 0.15 g/g creatinine and that a lower PCR is more suitable than previously considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption is based on incomplete evidence, and no validation studies are available. The latest studies of the relationship between ACR and PCR have indicated that an ACR of 30 mg/g creatinine is equal to a PCR of slightly lower than 0.15 g/g creatinine (Yamamoto et al 2011(Yamamoto et al , 2014Fisher et al 2013). These results challenge the validity of the PCR-based classification method recommended by the Japanese CKD guideline.…”
Section: Introductionmentioning
confidence: 99%